ELEMENTS OF FEEDBACK IN DISTANCE LEARNING (Multidisciplinary Journal of Science and Technology, 2024)
The effectiveness of distance learning hinges significantly on the quality of feedback provided to students. Feedback in this context serves not only as a tool for assessment but also as a means to guide, motivate, and engage learners. This article explores the key elements of feedback in distance learning, highlighting various types, delivery methods, and best practices to ensure it is both effective and meaningful.